Effect of Solution Viscosity on the Linear Optical Properties of Orcein Dye - Talib M. Abbas (Journal of Global Pharma Technology, 2018)
In this study, the effect of solution viscosity on the linear optical properties of the orcein was studied. For this purpose, different concentrations of the orcein solution were prepared in the ethanol solvent (1x10-3, 1x10-4, 1x10-5) Ml. After measuring the absorption and florescence spectra of three concentrations, the linear optical properties were identified. The results showing increasing absorption coefficient and refractive index with concentration increase. From florescence spectra, the life time of florescence energy level is increasing with concentration increase, and quantum yield decreasing with concentration increase. By varying the viscosity of the orcein solution -(1x10-3, 1x10-4, 1x10-5)Ml- by adding (2)ml of the glycerin, the absorption and florescence spectra of three concentrations with glycerin were measured and the linear optical properties were identified. The results showing increasing absorption coefficient and refractive index of each concentration after adding glycerin, except the absorption coefficient of (1x10-3Ml) concentration. While there was a decrease in life time quantum yield of florescence energy level of each concentration after adding glycerin, except the absorption coefficient of (1x10-3Ml) concentration.Keywords: Orcein, Absorption and Fluorescence spectra, Linear optical properties, Viscosity effect.